Taux de change et commerce : étude de droit international - Pantoja, Marina (Université Paris 10, 2019)
La relation entre la monnaie et le commerce, et l’impact que le taux de change peut avoir sur le droit du commerce international suscitent de vives discussions. la charte de la havane préconisait la non-utilisation de la dévaluation du taux de change comme une arme commerciale. le gatt contient des articles qui s’adressent aux questions de change. cependant, la thématique suscite des polémiques concernant notamment l’applicabilité des accords de l’omc comme un remède commercial contre la dévaluation anti-compétitive de la monnaie. d’un autre côté, le fmi, institution créée dans le cadre de l’accord de bretton woods, est l’organe compétent pour traiter les questions internationales d’ordre financier, et l’article iv de son statut concerne en particulier son devoir de surveillance des politiques de change de ses états-membres, afin d’éviter l’obtention d’avantages anti-compétitifs par des moyens de change. les deux organisations sont censées travailler de manière conjointe pour accomplir les objectifs de la croissance économique globale, et c’est dans cette conception que l’harmonisation entre le droit de l’omc et les directives du fmi doit être mise en place, pour que l’objectif primordial d’atteindre la gouvernance globale pour le bien de tous devienne une réalité.
Keywords: Competencia; Competition law; Concurrence; Concurrence (droit); Cooperation among the WTO and the IMF; Coopération OMC et FMI; Droit commercial (droit international); Droit du commerce international; Droit international économique; Fonds monétaire international; Guerre commerciale; International Economic Law; International trade law; Manipulation des taux de change; Manipulation of exchange rates; Organisation mondiale du commerce; Taux de change (manipulation); Trade war

Le consentement étatique à la compétence des juridictions internationales - Marquet, Clément (Université de Genève, 2019)
Le consentement étatique à la compétence des juridictions internationales est un élément incontournable du droit international public. Il régit le le fonctionnement de la justice internationale. Cependant, malgré son ubiquité, la notion est mal comprise. Ce travail, à travers la jurisprudence de la CIJ, d'ITLOS, de l'OMC et du CIRDI, redéfinit ce consentement, à la lumière de son histoire, son rôle et ses enjeux. Cette re-contextualisation est accompagnée d'une présentation et d'une analyse des enjeux contemporains entourant la notion.
Keywords: Arbitrage; Arbitragem; Arbitration; CIJ; CIRDI; Compétence; Compétence de la compétence; Consentement; Cour internationale de justice; Droit international public; Forum prorogatum; ICSID; ITLOS; Interprétation; Investissements; Investments; Juridictions; MFN; NPF; OMC; Organisation mondiale du commerce; Recevabilité; TIDM

Le principe d’interprétation autonome dans la Convention de Vienne sur les contrats de vente internationale de marchandises - Boussofara, Anissa (Université Côte d'Azur, 2019)
L’étude de l’interprétation de la Convention des Nations Unies sur les contrats de vente internationale de marchandises du 11 avril 1980 (CVIM) révèle la nécessité de la mise en œuvre d’un principe d’interprétation autonome, également affirmé dans d’autres instruments juridiques (conventions onusiennes, Principes UNIDROIT). Le principe d’interprétation autonome, inhérent au droit transnational, impose la prise en compte du caractère international des normes à interpréter ainsi que la promotion de leur uniformité d’application. Il s’agit ainsi d’assurer l’autonomie des termes du texte juridique à interpréter. Le comblement des lacunes du texte, qui constitue le second versant de l’interprétation juridique, est opéré par le recours aux principes généraux sous-tendant le texte. Le recours aux règles de droit interne n’aura lieu qu’en dernier ressort. L’étude se propose d’évaluer la mise en œuvre du principe d’interprétation autonome lors de l’application de la CVIM. A cette fin, il convient d’observer l’attitude du juge français lors de l’application du texte, non sans examiner la jurisprudence internationale ainsi que les sentences arbitrales l’appliquant également. Certaines dispositions et expressions conventionnelles ont été privilégiées afin d’examiner leur interprétation (par exemple : le contrat de fourniture, la contravention essentielle, le raisonnable, l’article 78 imposant l’application d’intérêts à toute somme due sans en fixer le taux). Le principe de bonne foi, guidant l’interprétation de la CVIM est également décortiqué dans sa relation avec l’interprétation de la CVIM. Il ressort de l’étude que la jurisprudence française méconnait le principe d’interprétation autonome lors de l’application de la CVIM. La comparaison avec d’autres juridictions montre que certaines d’entre elles font état d’une meilleure considération des règles d’interprétation édictées dans la Convention (Allemagne, Italie). La jurisprudence arbitrale révèle des sentences particulièrement enclines à la mise en œuvre du principe d’interprétation autonome sans que cette pratique ne soit uniforme. Les arbitres du commerce international sont souvent dotés d’une culture internationaliste et surtout, ils ne relèvent d’aucun ordre juridique national. Ils sont par conséquent beaucoup moins susceptibles d’être influencés par des références de droit interne et ainsi plus à même d’opérer une interprétation autonome des textes internationaux qu’ils mettent en œuvre. Ceci étant, l’affirmation explicite de l’application d’un principe d’interprétation autonome est quasiment inexistante dans la jurisprudence arbitrale comme dans celle des tribunaux étatiques.La présente étude a pour ambition d’élargir la connaissance du principe d’interprétation autonome par les interprètes du droit matériel uniforme en utilisant la CVIM comme support de démonstration. Le rôle du principe d’interprétation autonome sera fondamental dans l’expansion et la bonne application du droit uniforme. En effet, cette méthode d’interprétation est à même de respecter l’objectif du droit uniforme. When analyzing the United Nations Convention on Contracts for the International Sale of Goods adopted the 11 April 1980 (CISG), a principle of autonomous interpretation appears. This principle is stated in other legal texts (as United Nations conventions and UNIDROIT Principles). The principle of autonomous interpretation belongs to the transnational law and leads to take into account the international character of the legal provisions to be interpreted and to promote the uniformity of their application as “expressed” in the article 7 of the CISG. General principles underlying the CISG are used for gap-fillings which is the second side of legal interpretation. Using national laws is the ultimate resort.The principle of autonomous interpretation in the application of the CISG will be studied. For this purpose, judicial decisions and arbitral awards will be examined. Dispositions from the Convention have been chosen for their interpretation to be examined. The principle of good faith is also examined in its relation with the CISG interpretation. It will be observed that French case-law doesn’t acknowledge the principle of autonomous interpretation. Arbitral awards show a more important tendency to apply the principle of autonomous interpretation but there is no uniformity. The arbitrators in international trade have multicultural traditions and do not depend on a forum. Therefore they are less likely to be “influenced” by national “references” and so much more capable to interpret autonomously international dispositions. Nevertheless the “express” affirmation of a principle of autonomous interpretation is missing from arbitral awards and judicial decisions. This thesis aims to enlarge the acknowledgement of the principle of autonomous interpretation by the interpreters of uniform law using the CISG as a model. The function of the principle of autonomous interpretation will be fundamental to the expansion and to the correct application of uniform law. This method of interpretation is respectful of the objective of uniform law.
Keywords: Arbitrage; Arbitral Awards; Bonne foi (droit international); Commerce international; Contrats de vente internationale de marchandises; Convention des Nations unies; Droit international et droit interne; Droit transnational; France; Jurisprudence arbitrale; Lex mercatoria; Principe de bonne foi; The principle of good faith; Transnational law

Les manifestations juridiques et fiscales du protectionnisme de l'Union : essai sur un mode durable de régulation du libre-échange - Tran, Christophe (Université de Rennes 1, 2019)
Le droit de l’Union semble fondamentalement réticent à la résurgence du pendant antagoniste du libre-échange sous le vocable générique de protectionnisme. Pourtant, les manifestations juridiques et fiscales de ce protectionnisme de l’Union existent, variées en qualité et en intensité, et interpellent le juriste quant à la finalité poursuivie par l’entité souveraine qui le met en œuvre. Volonté de protection d’un intérêt propre et supérieur à l’intérieur de ses frontières ou volonté de domination du commerce international par le truchement d’instruments de défense mis au service d’une guerre commerciale, le protectionnisme peut-il être juridiquement fondé ou économiquement et politiquement opportun ? La combinaison est-elle possible ? De manière prospective, l’exigence de développement durable intégrée dans le droit de l’Union, dont la pertinence s’affirme à la lumière de la crise écologique, exhorte le juriste à penser le protectionnisme sous un angle durable dépassant la simple dimension économique. C’est à ces hypothèses, en contrariété assumée – mais nuancée – avec les libertés de circulation irriguant le droit de l’Union, que cette recherche est consacrée.
Keywords: Compétence; Défense commerciale commune; Exception protectionniste; Intérêt de l’Union; Libre-échange; Pays de l'Union européenne; Protectionnisme; Régulation durable; Souveraineté; Souveraineté européenne

Harmonização das Regras de Execução do Acordo de Mediação Comercial Internacional - Carvalho, David França Ribeiro de (Universidade de São Paulo, 2019)
O acordo mediado é aquele alcançado pelas partes como resultado de um procedimento de mediação. Diversamente das sentenças arbitrais estrangeiras, as quais gozam de um instrumento global para seu reconhecimento e execução, sob os auspícios da Convenção de Nova York, os acordos mediados transnacionais não possuem um instrumento harmonizado ou uniformizado que lhes conferem a mesma segurança. A mediação é um método de resolução de conflitos cada dia mais utilizado nas relações comerciais transnacionais e o resultado alcançado pelas partes precisa ser provido de maior reconhecimento e exequibilidade transnacional. Assim, são apresentadas algumas questões conceituais sobre o reconhecimento e a execução dos acordos mediados comerciais transnacionais para, na sequência, evidenciando o fenômeno da transnormatividade e pluralidade normativa, apresentar o arcabouço jurídico existente e seus limites no âmbito europeu com a Diretiva Europeia 2008/52/CE e transnacional, com a Lei Modelo da UNCITRAL sobre Conciliação Comercial Internacional de 2002. Essas normas reforçam a importância da elaboração de instrumentos que possam melhor assegurar o reconhecimento e a execução dos acordos mediados transnacionais. São apresentados e examinados argumentos sobre a necessidade e eventuais formas para o reconhecimento e execução dos acordos mediados transnacionais, proporcionando um melhor acesso à justiça. Ao final, são evidenciadas formas para a harmonização/uniformização e contextualizada a questão no âmbito do ordenamento jurídico brasileiro.
Keywords: Acordo mediado transnacional; Cross-border enforcement; Harmonization; Harmonização; International commercial mediation; MARD; Mediación; Mediation; Mediação; Mediação comercial internacional; Médiation; Reconhecimento e execução; Transnational mediated settlement agreement

Third Party’s Intellectual Property Rights And The Seller’s Liability Under The United Nations Convention On International Sale Of Goods (CISG) And The Sale Of Goods Act (SGA) - Kiraz, Serife E. (University of Leicester, 2019)
This thesis is a comparative analysis of the provisions on the seller’s duty to deliver the goods free from any third-party intellectual property rights (IPRs) under the United Nations Conventions on the International Sale of Goods (CISG) and the UK Sale of Goods Act 1979 (SGA). As a consequence of technological advancement, there has been an increased observance of the interaction between intellectual property rights (IPRs), which are intangible property rights, and tangible goods. As a result of this interaction, growing numbers of goods, which are either subject to IPRs as a whole or that possess an IP-protected component, have become subject to sales agreements. The circulation of the goods around the world increases the likelihood that third-party IPRs over the goods will be infringed. This risk of infringement also raises the possibility that the application of IP law remedies will prevent the buyer from reselling or using the goods in question. This study is concerned with the question of how the sale of goods is affected by third-party IPRs, and it proposes to undertake a comparative analysis of the provisions that determine the seller’s liability when third-party IPRs arise in relation to goods that are sold under the CISG and the SGA. It seeks to determine which instrument offers sufficient protection that will benefit the buyer. In attempting to reveal the sufficient protection, it also undertakes a comparative analysis of the remedies that are available to the buyer under the CISG and the SGA when third-party IPRs over the goods are raised. With regard to the widely acceptance of the CISG by 89 states, and the dominant role of English law in commercial law and its preference as a governing law to most contracts, it is aimed to determine the differences and similarities between the CISG and the SGA, and the practical consequences of their application to the contracts when third-party IPRs over the goods arise. The thesis will seek to determine if the text of the relevant CISG articles can be improved and will accordingly formulate proposals that work towards this outcome.

Article 6.8 and Annex II of the WTO agreement on antidumping - Persoz, Dimitri (European University Institute, 2019)
Article 6.8 of the Antidumping Agreement (AD) allows domestic investigating authorities to make determinations on the basis of the best information available (BIA) when any interested party does not cooperate during an antidumping investigation under the discipline of Annex II of the AD. Since its introduction, this provision has been the source of extensive and neverending litigation in front of both domestic investigating authorities and the Dispute Settlement Body. In this thesis, we research to what extent the findings of the Panels and the Appellate Body regarding Article 6.8 AD are consistent with the mandate set out in Articles 3.2, 11 DSU and 17.6 AD and to what extent they are reasonable from an economic perspective. To answer the first question, we first discuss Articles 3.2, 11 DSU and 17.6 AD to establish what is the mandate of the Panels and the Appellate Body under the Dispute Settlement Body. We then examine the findings of the Panels and the Appellate Body in the interpretation of the seven terms of Article 6.8 AD under the previously established mandate. To answer the second question, we summarize the latest developments in the economic theory of adjudication and litigation. We then discuss the findings of the Panels and the Appellate Body using this economic standard. In the conclusion, we compare the results of our analysis with current negotiations on Article 6.8 AD in the Doha Round framework and further discuss the opportunity to create a single united international investigating authority.

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification